S-wave modelling of the Showa-Shinzan lava dome in Usu Volcano, Northern Japan, from seismic observations. Issue 3 (21st March 2022) - Takeo, Akiko; Nishida, Kiwamu; Aoyama, Hiroshi; Ishise, Motoko; Kai, Takeru; Kurihara, Ryo; Maeda, Takuto; Mizutani, Yuta; Nakashima, Yuki; Nagahara, Shogo; Wang, Xiaowen; Ye, Lingling; et al.
SUMMARY: To obtain an internal S -wave velocity structure, we conducted a passive seismic campaign with 21 1-Hz seismometers on and around the Showa-Shinzan lava dome, which emerged during the 1943–1945 eruption of Usu Volcano, Japan. Before the campaign, we calibrated seismometers and found slight phase-response differences between seismometers of less than 1–2°. After the campaign, we extracted seismic wavefield by taking cross-correlations of vertical-component ambient noise records between seismic sites. We developed a new method to measure phase velocities of the Rayleigh wave automatically by assuming layered structure and finally obtained 1-D S -wave velocity models in summit, roof and base regions. The obtained S -wave velocity right beneath the intruded lava dome is higher than that in surrounding areas by a few tens of per cent down to a few hundred metres below sea level, indicating narrow but deep existence of the root of the lava dome. The obtained S -wave velocity at depths shallower than ∼50 m inside the lava dome in the summit area was ∼1 km s −1, significantly lower than that predicted from the density of  2.3 × 10 3  kg m −3 estimated in previous muon-radiography studies and a conventional scaling, indicating the effect of cracking in the lava dome.